Orthorhombic YBa2Cu3O7−δ superconductor with TiO2 nanoparticle addition: crystal structure, electric resistivity, and AC susceptibility - Barood, Fatma; Kechik, Mohd Mustafa Awang; Tee, Tan Sin; Kien, Chen Soo; Pah, Lim Kean; Hong, Kai Jeat; Shaari, Abdul Halim; Baqiah, Hussein; Abdul Karim, Muhammad Khalis; Shabdin, Muhammad Kashfi; Mohd Shariff, Khairul Khaizi; Hashim, Azhan; et al. (Multidisciplinary Digital Publishing Institute, 2023)
This article reports the effect of a nanoscale addition of TiO2 on the structure and superconducting parameters of the high-temperature superconductor YBa2Cu3O7-δ (Y123). Polycrystalline compounds of Y123 with different percentages of TiO2, x = 0.0, 0.2, 0.4, 0.6, 0.8, and 1.0, were fabricated using the thermal treatment method. An analysis using X-ray diffraction confirmed the formation of Y123 phases for all composite samples. Field-emission scanning electron microscopy (FESEM) analysis revealed the growth of grain size and decrease in porosity, with a sign of partial melting of grains for the samples with TiO2 addition. The magnetic and electric transport properties were investigated using AC susceptibility measurement and the four-probe method, respectively. It was observed that the superconducting transition temperature, Tc-onset, for a pure sample determined by ACS and 4PP was 95.6 K and 95.4 K, respectively. These values were found to decrease with the addition of TiO2, while the superconducting transition (∆Tc) improved with TiO2 addition except for the sample at x = 0.2 wt.%, which showed the broadest transition width. The sharpest superconducting transition (∆Tc) was observed for the sample at x = 1.0 wt.%, indicating that the addition of TiO2 nanoparticles is expected to serve as artificial pinning centres and strengthen the connection among the grains in the Y123 ceramic.